Sejarah dan Revitalisasi Perjuangan Pertanian Nahdlatul Ulama Melawan Ketidakadilan Agraria - Ahmad Nashih Luthfi (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Abstract: Historiographically, there is false understanding that the 1960’s landreform in Indonesia was only supported by communism party, and religion-based parties were on the opposite sides, ideologically and sociologically. This article contradicts the simplification of the understanding of the history by pointed out that Nahdlatul Ulama supported the policy of land reform. The support was within the framework of the creation of justice, as well as the understanding that private land ownership is respected in Islam, as part of the goal in enforcing syari’at: to keep the possessions of the umat (hifdhul maal). Not only on the implementation, Pertanu also defend and fight for the peasants when they were expelled, and their lands were taken over (counter-landreform) post 1965. Based on the archived of ANRI and local military documents, this article record the institutional history of Pertanu and its struggle to defent the peasants after 1965, and the dynamic of the implementation of land reform and its backflow in Banyuwangi, East Java. The description of historical experiences of this peasant organization is equipped by contextual reflection and its revitalization on current era when facing contemporary agrarian issues.